2016
DOI: 10.1016/j.archger.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in 20 years of medication use in older adults: Findings from three elderly cohorts in Stockholm, Sweden

Abstract: New drugs and expanded drug indications are constantly being introduced. Welfare states strive to provide equity in drug treatment for all of its citizens and today´s healthcare systems spend financial resources on drugs for the elderly in a higher rate than for any other age group. Drug utilization in elderly persons has an impact in health and wellbeing in older

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
23
1
Order By: Relevance
“…A Finnish study [24] also reported unchanged prevalences of overall psychotropic drug use between 1990-91 and 1998-99 and a Swedish study [25] observed unchanged prevalences among cognitive intact elderly, but significant rises among cognitive impaired elderly between 1987 and 2007. Contrarily, significant increases in overall psychotropic drug use were reported by an US [26] and a Spanish study [27].…”
Section: Discussionmentioning
confidence: 99%
“…A Finnish study [24] also reported unchanged prevalences of overall psychotropic drug use between 1990-91 and 1998-99 and a Swedish study [25] observed unchanged prevalences among cognitive intact elderly, but significant rises among cognitive impaired elderly between 1987 and 2007. Contrarily, significant increases in overall psychotropic drug use were reported by an US [26] and a Spanish study [27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, debate regarding polypharmacy among old people has been intense [ 1 ]. Haider et al [ 2 ] showed that the prevalence of polypharmacy (use of five or more drugs) in individuals aged ≥ 77 years increased from 18 to 42% during the 1992–2002 period.…”
Section: Introductionmentioning
confidence: 99%
“…Both the extent and the pattern of drug use differs between females and males: According to SNAC-K (Swedish National Study on Aging and Care in Kungsholmen), in Stockholm in 2007 [ 1 ], 51.4% of the females and 33.2% of the males received analgesics. The corresponding percentages for psychotropic drugs were 48.3% for females and 30.8% for males.…”
Section: Introductionmentioning
confidence: 99%
“…Women were more likely to take analgesics, TCAs and SSRIs, compared with men. Craftman et al 36 reported similar findings when they examined medication usage in older adults, over a 20-year period. One possible explanation for our analgesic findings could be that there are gender differences in relation to pain.…”
Section: Discussionmentioning
confidence: 70%